2019
DOI: 10.3389/fpsyg.2019.00819
|View full text |Cite
|
Sign up to set email alerts
|

Family Socioeconomic Status and Adolescent Depressive Symptoms in a Chinese Low– and Middle– Income Sample: The Indirect Effects of Maternal Care and Adolescent Sense of Coherence

Abstract: The current study investigated whether socioeconomic status (SES) was associated with adolescent depressive symptoms through maternal parenting and adolescent sense of coherence (SOC). Using a sample of 1220 Chinese adolescents, it was found that SES, maternal care, and adolescent SOC were positively related to each other and negatively related to adolescent depressive symptoms, respectively. Maternal control was positively related to adolescent depressive symptoms and negatively related to their SOC, but not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 68 publications
(74 reference statements)
2
16
0
1
Order By: Relevance
“…Moreover, adolescent mothers in SSA tend to experience greater barriers and stigma in navigating health services , being taken seriously by the health workers and relatives, which further exacerbates their stress and negative parenthood experience [ 24 27 ]. These cumulative stressors experienced during adolescent motherhood aggravates parenting stress [ 28 ] and increase the risk for depression [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, adolescent mothers in SSA tend to experience greater barriers and stigma in navigating health services , being taken seriously by the health workers and relatives, which further exacerbates their stress and negative parenthood experience [ 24 27 ]. These cumulative stressors experienced during adolescent motherhood aggravates parenting stress [ 28 ] and increase the risk for depression [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, social inequalities in adolescents' wellbeing are often measured by examining disparities in adolescents' socioeconomic status (SES) while social capital is largely overlooked. Socioeconomic status (SES) has been found to impact health and wellbeing directly [2,[8][9][10][11] and indirectly through psychosocial factors such as the poor's inability to establish bonds and networks for their benefits [6,7,11]. These psychosocial factors, however, can function as protective mechanisms to offset some effects of SES inequalities on wellbeing.…”
Section: Introductionmentioning
confidence: 99%
“…Another study found inverse associations between PTS symptoms and strong SOC and supported the idea that SOC is strongly related to mental health [ 36 ]. Additionally, the study using analysis of structural equation modeling found that SES was associated with adolescent depressive symptoms indirectly through maternal care separately, as well as through maternal care and adolescent SOC sequentially [ 37 ]. Furthermore, a recent study found that adolescents with a weaker sense of coherence and a tendency toward depression were much more likely to become addicted to energy drinks, while a strong sense of coherence diminishes the effects of depression [ 20 ].…”
Section: Discussionmentioning
confidence: 99%